Multilayer framework for digital multicomponent platform design for colorectal survivors and carers: a qualitative study - Melhem, Samar J.; Kayyali, Reem (Frontiers in Public Health, 2023)
Background: The advent of eHealth services offers the potential to support colorectal cancer (CRC) survivors and their informal caregivers (ICs), yet research into user needs and design requirements remains scant. This exploratory qualitative study addresses this knowledge gap by focusing on the development of a Digital Multicomponent Platform (DMP) designed to provide comprehensive support to these populations.Aims: The objective of this research is to use qualitative methodologies to identify key user needs and design requirements for eHealth services. It seeks to propose and apply a multitiered framework for creating a DMP that encapsulates the needs of CRC survivors and their ICs.Methods: Skype-based focus groups (FGs) were utilised to gather qualitative data from CRC survivors and ICs. This approach served to elicit crucial themes integral to the design of the DMP. A multi-tiered framework was subsequently developed to integrate user-centred design (UCD) principles and requirements with predetermined outcomes, eHealth services, and IT infrastructure.Results: The first stage of the analysis identified five crucial themes: 1) the importance of healthcare system interaction via eHealth,2) interaction between healthcare providers and peers, 3) lifestyle and wellness considerations, 4) platform content and user interface requirements, 5) caregiver support. The second stage analysis applied the multi-tiered framework, to determine the DMP that was conceptualised from these themes, underscores the significance of personalised content, caregiver involvement, and integration with electronic health records (EHRs).Conclusions: The study offers novel insights into the design and development of digital supportive care interventions for CRC survivors and their caregivers. The results highlight the utility of user-centred design principles, the significance of personalised content and caregiver involvement, and the need for a unified health data platform that promotes communication among patients, healthcare providers, and peers. This multi-tiered framework could serve as a prototype for future eHealth service designs.